A Solar Water Heater Using a Two-Stage Thermostat as a Pre-Heating System for a Feed Plant - Keh-Chin Chang; Wei-Min Lin; Kung-Ming Chung (Journal of Energy Conservation, 2026)
Solar thermal heating is a mature technology for producing hot water in the domestic sector. Industrial processes require significant heat, so solar water heaters can be used for pre-heating. A forced- circulation solar water heater is installed in a feed plant that is located south of the Tropic of Cancer. The thermal efficiency of the system is closely related to the incident solar radiation. This study uses a two-stage setting for a thermostat to collect more solar energy if incident solar radiation is less intense. When the temperature difference between the water storage tank and the water outlet for the solar collectors (setting of a thermostat from 6° to 8°C) increases, there are more energy savings. The simple payback period for the system is 2.05 years, so it is financially viable to use a solar water heater for industrial heat processes. Excessive carbon emissions resulting from industry processes are a main cause of global warming. Carbon tax can be used as a central climate policy instrument for carbon reduction. The government of Taiwan stipulates the legal foundation for levying carbon fees in 2025. The carbon emissions and carbon tax for the feed plant are described to prompt the case for sustainability.
Keywords: solar thermal